Evaluation of Chicken Bone-Derived CaO Catalyst for biodiesel production from waste cooking oil - Mufandi, Ilham; Kholis, Muhammad Nur; Rahmawan, Arief; Suntivarakorn, Ratchaphon; Nugraha, Dhaifullah Nafis; Alana P, Raka Wyztyo (Eksergi, 2024)
This research explores the use of waste cooking oil (WCO) into biodiesel and adding a calcium oxide (CaO) catalyst derived from chicken bone waste. The synthesized CaO catalyst was characterized using FTIR and SEM to determine its structural and chemical properties. Biodiesel production experiments were carried out at a temperature of 60°C with an oil-to-methanol ratio of 9:1 and a CaO catalyst load of 5% concentration. The biodiesel produced is characterized by its main quality parameters, including flash point, density, acid number, viscosity, and heating value. The research results show that the CaO catalyst contains various organic compounds, including haloalkanes, 1,2-disubstituted functional groups, primary alcohols, aromatic compounds, and alcohols. In addition, the CaO catalyst contains mineral compositions such as calcium, carbon, oxygen, sodium, magnesium, and phosphorus. Biodiesel yield increases significantly with increasing catalyst loading, reaching a maximum of 92.70% at 15% catalyst loading. This research shows the effectiveness of the CaO catalyst derived from chicken bone waste for environmentally friendly biodiesel production using microwave technology.